2019
DOI: 10.18510/hssr.2019.7541
|View full text |Cite
|
Sign up to set email alerts
|

Issues and Challenges of Future Newspapers

Abstract: Purpose of the study: This paper reviews recent literature on issues and challenges of the future newspaper. It traces issues and challenges that generally impacting the journalism industry worldwide and may be applied for future studies that shall further examine this matter empirically. Methodology: This is a discussion paper that does not apply any research method. The discussion is done based on recent reviews related to the issue of the future of the newspaper and its trend. Main Findings: Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In addition, scholars have also included other advantages such as its ability to foster autonomous learning and enhance collaborations among participants of the course (Guth & Helm, 2010;Yusnimar, 2019), for instance, suggested that learners showed positive reactions to online classroom and presented equal performance to the traditional classroom settings. It is merely due to the demands of technology and other factors, there is no denying that today, changes arise in communication's form or platforms compared to the previous years (Othman, et al, 2019). In some cases, where student's computer literacy was limited, CALL tends to come up with potential downsides.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, scholars have also included other advantages such as its ability to foster autonomous learning and enhance collaborations among participants of the course (Guth & Helm, 2010;Yusnimar, 2019), for instance, suggested that learners showed positive reactions to online classroom and presented equal performance to the traditional classroom settings. It is merely due to the demands of technology and other factors, there is no denying that today, changes arise in communication's form or platforms compared to the previous years (Othman, et al, 2019). In some cases, where student's computer literacy was limited, CALL tends to come up with potential downsides.…”
Section: Introductionmentioning
confidence: 99%
“…Since the media can reach wider audiences [20], the media have the power to change audiences' viewpoints [25] [26] [20], either influencing positively by providing evidence-based information to the public [27] or negatively by presenting fake news (hoaxes) and acting against the government's programs [28] by spreading unreliable rumors [27]. Hoax news is perilous [29] and it causes significant negative social effects [30] because it is aimed to deceive and create misunderstanding among readers [31].…”
Section: The Media Effectmentioning
confidence: 99%
“…Nowadays, people tend to prefer reading in the form of online social media to print media (Othman et al, 2019). A study conducted by Obaidillah and Rahman (2018) on the impact of the internet and social media on students' reading habits indicated that students spend more hours on electronic media than on reading books.…”
Section: Literature Reviewmentioning
confidence: 99%